Optimization of Parameters for Increased Production of Polyhydroxybutyrate (PHB) from Bacillus Species - Panchali Sarma; Pooja Shinde; Dr. Shampa Chakraborti (International Journal of Pharma and Bio Sciences, 2020)
Polyhydroxybutyrate (PHB) granules produced as a product of carbon assimilation from glucose serve as energy storage molecules in bacteria, particularly in the absence of nutrients. PHB is used to produce bioplastics due to its biodegradability. Due to the low conversion of carbon sources to PHB, optimization of the culture media, pH, temperature, etc. and utilization of promising low-cost carbon sources are essential to increase the PHB yield and reduce the cost associated with bioplastics production. The present work aimed at the maximization of PHB yield from the Bacillus spp using various alternative cheap carbon sources. A reference bacterial strain, viz., Bacillus megaterium MCC 2197(T) was procured from the National Centre for Microbial Resource, Pune. The study used Jaggery, Neera, Chikoo, Sago and Wheat bran as alternative cheap carbon sources for the production of PHB. The maximum yields of PHB obtained were 0.065 g/100 ml and 0.043 g/100 ml from Bacillus spp and the reference strain using Jaggery and Sago as carbon sources respectively with ammonium sulphate as the nitrogen source at pH 7 and a temperature of 370 C in comparison with 0.034 g/100 ml and 0.022 g/100 ml of PHB using glucose (control) as a carbon source. The study found that Yeast Extract Glucose Medium (YEGM) and Nutrient Broth (NB) were the best media for PHB production for the Bacillus spp and Bacillus megaterium respectively. The results of this study thus confirmed that cheap alternative carbon sources under optimized conditions could significantly increase the yield of PHB from the Bacillus species.